Patient with diabetic ketoacidosis - Natalia Świątoniowska; Paulina Tylak; Ewelina Bartosiak; Izabella Czykieta; Beata Jankowska-Polańska (Kazimierz Wielki University, 2019)
Ketoacidosis is a life threatening condition caused by hyperglycemia. It affects approximately 15-70% of patients with diabetes. A patient with ketoacidosis requires intensive treatment, monitoring and constant nursing care. The aim of the study was to present the most important patient care issues associated with ketoacidosis based on the International Classification for Nursing Practice ICNP®.